Commentary on "A Computational Approach to the Detection and Prediction of (Ir)Regularity in Children’s Folk Songs" - Cancino-Chacon, Carlos Eduardo (Empirical Musicology Review, 2023)
This commentary on "A Computational Approach to the Detection and Prediction of (Ir)Regularity in Children's Folk Songs" by Mihelač, Povoh, and Wiggins reflects on the use of methods of (statistical) expectation to analyze musical structure and regularity, including potential biases of such methods, and provides some perspectives on leveraging information theoretic models of musical expectation to design cognitively plausible computational listeners of music.